Implementation of the Public Service Application Program at the Manado City Health Office - Nora Santy Rembet; Agustinus B. Pati; Michael Mamentu (Journal of Public Administration and Government, 2023)
This research is about the implementation of public service application programs at the Manado City Health Office. In order to follow up on the mayor's policy, the Manado City Health Office digitized health services by developing the Manado City Health Service website application, namely dinkes.manadokota.go.id, which is in the domain www.manadokota.go.id. The display that can be seen at this time is the availability of health information data through the Manado City Health Office website application at http://dinkes.manadokota.go.id, but the information display is very minimal and not up-to-date. The problem is that since the Health Service application was opened, this website has only seen 769 views. This is a sign of the low level of utilization of this digital health information service. This study aims to determine the implementation of public service application programs at the Manado City Health Office. This study uses a qualitative descriptive approach that refers to the theory of policy implementation from Jones (1984) which shows that the results of public service application programs have not been optimal, namely the health service website at the Manado City Health Office caused by 1) determinant factors in the form of an organization or team formed and the website management team is not supported by competent human resources, a fixed budget, with policy infrastructure according to needs, 2) counter-productive attitudes towards duties and obligations, 3) and the implementation of the health service application website program is not developed due to the absence a clear vision, the absence of definite budgetary support, as well as changes in the replacement of leadership which also in turn influenced the policy direction of the Manado City Health Office.